A geology for engineers - Blyth, F. G. H.; De Freitas, M. H. (Elsevier, Butterworth-Heinemann, 1984)
"This seventh edition of 'A Geology for Engineers' has been written to provide students of engineering with a recent text in geology for use during their first degree in Civil Engineering or Mining. As with previous editions, we have attempted to explain both the subject of geology and its relevance to engineering work in rock and soil... Three new chapters have been written and the structure and content of former chapters have been substantially changed. Much attention has been devoted to the quality of illustrations and tabulated data, and most of the artwork has been redrawn, SI units have been used throughout the text"--Preface.
Keywords: Engineering geology.; elektronické knihy; electronic books